Specific Features of Formation of Electron and Hole Trapping Centers in Irradiated CaSO4-Mn and BaSO4-Mn - Turlybek. N. Nurakhmetov; Temirulan. T. Alibay; Keleshek. B. Zhangylyssov; Dulat. H. Daurenbekov; Amangeldy. M. Zhunusbekov; Aset. Zh. Kainarbay; Batsaiy. M. Sadykova; Doszhan. A. Tolekov; Raushan. K. Shamiyeva (Crystals, 2023)
Spectroscopic and thermoactivation methods were used to study the processes of accumulation of electron and hole trapping centers and energy transfer of electronic excitations to impurities in <semantics>CaSO4<mtext>-</mtext>Mn</semantics> and <semantics>BaSO4<mtext>-</mtext>Mn</semantics>. It is shown that electronic trapping centers are created during the excitation of an anionic complex as a result of charge transfer from <semantics>O2−→<msubsup>SO42−</msubsup></semantics> to closely spaced anionic complexes <semantics><msubsup>SO42−</msubsup></semantics> in <semantics>CaSO4</semantics> and <semantics>BaSO4</semantics>. In <semantics>CaSO4</semantics> and <semantics>BaSO4</semantics>, energy transfer from the host to impurities occurs at the moment of charge transfer from the excited anionic complex to the combined radiative electronic state at 2.95–3.1 eV. This combined state is formed from electronic trapping centers <semantics>Mn+<mtext>-</mtext><msubsup>SO4−</msubsup></semantics> and <semantics><msubsup>SO43−</msubsup><mtext>-</mtext><msubsup>SO4−</msubsup></semantics>. It was found that the emerging combined radiative states at 2.95–3.1 eV of sulfates, which are formed as a result of charge transfer from the excited anionic complexes to the excited state of impurities, <semantics>Tl+,Cu+,and Mn2+</semantics>, occupy the same energy levels as the intrinsic electronic trapping center <semantics><msubsup>SO43−</msubsup></semantics> of the host at 2.95–3.17 eV. Experimental results show that during UV photon irradiation, anionic complexes are excited mainly near impurities in sulfates.